2009
DOI: 10.1111/j.1365-2141.2009.07855.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic mutations associated with mild and severe deficiencies of transcobalamin I (haptocorrin) that cause mildly and severely low serum cobalamin levels

Abstract: Summary Transcobalamin (TC) I deficiency, like the function of TC I itself, is incompletely understood. It produces low serum cobalamin levels indistinguishable from those of true cobalamin deficiency. Diagnosis is especially elusive when TC I deficiency is mild. To provide new, more substantive definition, the TCN1 gene was examined in two well‐characterised families that included members with both severe and mild TC I deficiencies. A severely deficient proposita with undetectable TC I levels displayed compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…18 More work needs to be done to sort out the genetics and pathophysiology related to cobalamin deficiency. 19 Some, but not all, studies have found marginally better performance (as assessed by receiver operator curves) by holoTC when compared with serum B 12 .…”
Section: Discussionmentioning
confidence: 99%
“…18 More work needs to be done to sort out the genetics and pathophysiology related to cobalamin deficiency. 19 Some, but not all, studies have found marginally better performance (as assessed by receiver operator curves) by holoTC when compared with serum B 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Both the TC I and ß-globin genes are located on chromosome 11, but linkage dysequilibrium is unlikely because their locations are far apart (11q12-13 and 11p15, respectively) and their mutation dosages do not match in many cases (Table II). Pending clarification of TC I function and organization of large prospective surveys applying appropriate assays17 and genetic tools,24,31 the association between TC I deficiency and sickle cell disease may turn out to be indirect, perhaps involving an unidentified selection pressure.…”
Section: Patient 2 (Table I)mentioning
confidence: 99%
“…]. Homozygosity and compound heterozygosity cause absence of transcobalamin I, thereby inducing cobalamin levels less than 100 ng/l; these are typically misdiagnosed and treated as cobalamin deficiency [19]. Simple heterozygosity decreases transcobalamin I and cobalamin modestly and mimics SCCD [18-21,22 & ].…”
Section: Nonnutritional Influences On Biomarkersmentioning
confidence: 99%